To write the equation of the quadratic function in vertex form \( f(x) = a(x - h)^2 + k \), we first need to identify the vertex \((h, k)\) and the value of \( a \).
From the information provided, we know that the vertex of the parabola is at the point \((1, -6)\). Therefore, \( h = 1 \) and \( k = -6 \).
Now, the equation looks like this: \[ f(x) = a(x - 1)^2 - 6 \]
Next, we can use another point on the graph to find the value of \( a \). The point \((0, 0)\) lies on the graph, which means \( f(0) = 0 \).
Substituting \( x = 0 \) and \( f(0) = 0 \) into the equation gives us: \[ 0 = a(0 - 1)^2 - 6 \] \[ 0 = a(1) - 6 \] \[ a - 6 = 0 \] \[ a = 6 \]
Now we can substitute \( a \) back into our equation: \[ f(x) = 6(x - 1)^2 - 6 \]
So, the equation of the quadratic function in vertex form is: \[ f(x) = 6(x - 1)^2 - 6 \]